Development And Validation Of Rp-Hplc Method For The Estimation Of Bumetanide In Tablet Formulation - Sethi, Reeta; Paul , Yash; Goyal, Surinder (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A remarkably simple, selective and precise method to determine bumetanide in tablet dosage form was developed and validated using Reverse Phase High Performance Liquid Chromatography (RP HPLC). The LC separations was achieved on a bondapak C18 column in the isocratic mode using Glacial acetic acid: Tetrahydrofuran: Water: Methanol (2:5:45:50 v/v/v/v), as a mobile phase at flow rate 1.0 mL/min with UV detection at 254 nm. The retention time for bumetanide was 11.3 min. The method was validated by determining its sensitivity, precision, accuracy as per ICH guidelines. The % recovery was found to be as is simple, rapid, precise and accurate and hence, can be applied for routine quality control analysis of this drug in tablet dosage form.